The clinician's guide to anxiety sensitivity treatment and assessment - Smits, Jasper A. J.; Otto, Michael W.; Powers, Mark; Baird, Scarlett (Academic Press, an imprint of Elsevier, 2019)
The Clinician's Guide to Anxiety Sensitivity Treatment and Assessment provides evidence-based strategies for clinicians looking to treat, assess and better understand anxiety sensitivity in their patients. The book delivers detailed guidance on the theoretical background and empirical support for anxiety sensitivity treatment methods, assessment strategies, and how clinicians can best prepare for sessions with their clients. Bolstered by case studies throughout, it highlights anxiety sensitivity as a transdiagnostic risk factor while also looking at the importance of lower-order sensitivity factors (physical, social, cognitive) in treatment planning, implementation and evaluation.